Factors associated with common mental disorders among farmers in a medium-sized municipality in Northeastern Brazil - Roberta Machado Alves; Emelynne Gabrielly de Oliveira Santos; Isabelle Ribeiro Barbosa (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To identify the prevalence and factors associated with common mental disorders among farmers living in a medium-sized municipality in Northeastern Brazil between 2019 and 2020. METHODS Trained interviewers applied the standardized questionnaire in 450 participants. Sociodemographic, health, income and working characteristics were assessed. The screening of common mental disorders was performed using the Self-Reporting Questionaire, with the cutoff point ≥ 7 for women and ≥ 5 for men. Poisson regression with robust estimation was applied to verify the prevalence ratios in the bivariate and multivariate analysis. RESULTS The prevalence of common mental disorders among farmers was 55.1% (95%CI: 50.4-59.6). The variables that remained significant and associated with common mental disorders were: men (PR = 1.7), > 60 years old (PR = 0.5), poor or very poor self-assessment of health (PR = 1.4), previous mental health treatment (PR = 1.2), alcohol abuse (PR = 1.2) and loss of production (PR = 1.3). CONCLUSION These results indicate that common mental disorders are associated with individual factors and with the farmers' context of life and work, which shows the importance of social, economic and health services support to this group of workers.